Polimorfismos en el extremo 5´ del gen WDTC1 y su asociación con el espesor de grasa dorsal en cerdos Landrace - Fassa, M.B. (2020)
The WDTC1 (WD and tetratricopeptide repeats 1) gene has an anti-adipogenic function, converting it into a candidate gene to explain the phenotypic variation in traits of economic importance for swine breeding. The objective of this work was to identify and evaluate the effect of single nucleotide polymorphisms (SNPs) located in the 5`UTR region of WDTC1 and its association with backfat thickness (BFT) in 128 Landrace pigs. For the identification of SNPs, 808 bp (from 84,466,928 to 84,467,736 of sequence NC010448.4 of GenBank) were amplified, sequenced and analyzed by multiple alignments. The polymorphisms found were: SNP1 (T / C, 84.466.982), SNP2 (C / T, 84.467.066), SNP3 (T / C 84.467.131), SNP4 (C / T, 84.467.201), SNP5 (G / T, 84.467.368), SNP6 (C / A, 84.467.402) and SNP7 (G / A, 84.467.413). Statistical analysis was performed using ANOVA only for the SNP1. The differences were significant among genotypes of SNP 1 (p-value <0.05) for (BFT). These results indicate that the 5' UTR region of WDTC1 is polymorph and the SNP1 would be associated with the phenotypic expression of the character analyzed.